THE EFFECT OF MEDIA AND INFORMATION LITERACY TOWARDS THE RESPONSE OF HOAX INFORMATION VIA WHATSAPP - Minarso, Christinia; Irawati, Indira (BACA: Jurnal Dokumentasi dan Informasi, 2021)
Women's ability in using technology must be completed with a good literacy to respond critically towards hoax information on WhatsApp. Likewise, the Empowerment and Family Welfare movement or Pemberdayaan Kesejahteraan Keluarga (PKK) in Situbondo, where most of the driving teams are housewives who use WhatsApp applications as their group communication. Therefore, the purposes of this study were: 1) to identify the Media and Information Literacy (MIL) of PKK Driving Team in Situbondo and hoax information responses on WhatsApp, 2) to examine the effect of MIL of PKK Driving Team in Situbondo towards hoax information responses on WhatsApp, 3) to investigate the effect of MIL of PKK Driving Team in Situbondo to the cognitive, affective, and behavioral responses of hoax information via WhatsApp. The research method used was a quantitative method with 440 respondents. The results revealed that: 1) the MIL was quite high, but the responses of hoax information were quite low, 2) there was a positive and significant effect of MIL towards hoax information responses, 3) there was a positive and significant effect of MIL to the cognitive, affective, and behavioral responses. This study provides an insight in making MIL policies for empowering PKK Driving Team in Situbondo in responding to hoax information critically and wisely.